2012
DOI: 10.4049/jimmunol.1102786
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: IL-21 Derived from Human Follicular Helper T Cells Acts as a Survival Factor for Secondary Lymphoid Organ, but Not for Bone Marrow, Plasma Cells

Abstract: IL-21 induces the differentiation of activated B lymphocytes into plasma cells (PC), but its direct effect on PC remains uncertain. This study analyzes the role of IL-21 on human in vivo-generated PC. IL-21R was clearly expressed on PC from the human tonsil, the lymph node, and the spleen (secondary lymphoid organs [SLO]) but barely on terminally mature bone marrow PC. IL-21 enhanced Ig secretion by isolated SLO PC but not bone marrow PC. Tonsillar T follicular helper (Tfh) lymphocytes are known to secrete IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 24 publications
3
42
0
Order By: Relevance
“…Subsequently, CD31 + cells were purified from the To non-T cell fraction by immunomagnetic cell selection to pre-enrich PC (17,32 …”
Section: Cell Preparation and Cell Sortingmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, CD31 + cells were purified from the To non-T cell fraction by immunomagnetic cell selection to pre-enrich PC (17,32 …”
Section: Cell Preparation and Cell Sortingmentioning
confidence: 99%
“…The different auxiliary cell types, and the cytokines and other molecules reported as participants in PC survival niches have been recently revised (24,31). In a previous study, we have demonstrated that human SLO, but not BM, PCs express IL-21R and respond to IL-21 by activating STAT-3 and increasing their survival (32). IL-10 induces the differentiation of B lymphocytes to PCs (33); nevertheless, its role in PCs has not been clarified.…”
mentioning
confidence: 99%
“…IL-21 has been suggested to play an important role in T FH differentiation (Rodríguez-Bayona et al, 2012). We showed that stimulation with CpG-DNA enhanced IL-21 production that was (predominantly IgG), but were unable to help naïve B cells (Bentebibel et al, 2013).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 88%
“…Additionally, this effect was impaired when T FH cell-derived IL-21 was blocked. 26 Additionally, IgE and other immunoglobulin isotypes were observed to be switched under the influence of T cell-derived cytokines. 24 For instance, IL-10 was identified as the switch factor for IgG4, 27 and IL-21 was shown to be the switch factor for human IgG1 and IgG3.…”
Section: Pc Differentiation: the Importance Of T Cells Cytokines Andmentioning
confidence: 99%
“…76 However, the changes in Bcl-6 expression in autoimmune disease remain disputed. Studies have reported elevated Bcl-6 mRNA levels in the CD4 1 T cells of RA patients 26 and SLEprone mice. 69 The breakdown of the Blimp-1 and Bcl-6 balance leads to auto-PC accumulation, which tends to cause autoimmune disease.…”
Section: Il-21/il-21r and Slementioning
confidence: 99%